On the Dating of the Architectural Monuments of Hellenistic Myrmekion - Kolosov, Vladimir P. (Actual Problems of Theory and History of Art, 2023)
The article is dedicated to the questions of the attribution of two large architectural blocks, which were parts of a Doric entablature of one building, discovered in 1937 in Myrmekion. Until the present day, these fragments remain the most prominent examples of Doric architecture found at the archaeological site. These details were dated to the late Classical period based on the available comparative material. Researchers used nine Doric structures from the 4th to 3rd centuries BC as analogies for their analysis, focusing on the proportions of architectural elements. Modern data processing capabilities allow for a broader range of analogies and a more comprehensive analysis of changes in a significantly larger number of features. This work examines more than 60 Doric structures dated from the 4th to 2nd centuries BC as comparative material and evaluates their differences in entablature design. During the analysis, the most significant datable criteria and their distribution among the sample objects were determined. As a result, a comprehensive picture of the regional and chronological characteristics of Doric structures from the Late Classical and Hellenistic periods was obtained. The identified analogies allowed for the dating of the architectural fragments from Myrmekion to the second half of the 3rd century BC.
Keywords: Northern Black Sea; Bosporan Kingdom; Doric order; Myrmekion; Hellenism; entablature; antique architecture; triglyph; architrave; frieze